Novel Antibody Drug Conjugates Targeting Tumor-Associated Receptor Tyrosine Kinase ROR2 by Functional Screening of Fully Human Antibody Libraries Using Transpo-mAb Display on Progenitor B Cells - Hellmann, Ina; Waldmeier, Lorenz; Bannwarth-Escher, Marie-Christine; Maslova, Kseniya; Wolter, Fabian I.; Grawunder, Ulf; Beerli, Roger R. (Frontiers in Immunology, 2018)
Receptor tyrosine kinase-like orphan receptor 2 (ROR2) has been identified as a highly relevant tumor-associated antigen in a variety of cancer indications of high unmet medical need, including renal cell carcinoma and osteosarcoma, making it an attractive target for targeted cancer therapy. Here, we describe the de novo discovery of fully human ROR2-specific antibodies and potent antibody drug conjugates (ADCs) derived thereof by combining antibody discovery from immune libraries of human immunoglobulin transgenic animals using the Transpo-mAb mammalian cell-based IgG display platform with functional screening for internalizing antibodies using a secondary ADC assay. The discovery strategy entailed immunization of transgenic mice with the cancer antigen ROR2, harboring transgenic IgH and IgL chain gene loci with limited number of fully human V, D and J gene segments. This was followed by recovering antibody repertoires from the immunized animals, expressing and screening them as full-length human IgG libraries by transposon-mediated display in progenitor B lymphocytes ("Transpo-mAb Display") for ROR2 binding. Individual cellular "Transpo-mAb" clones isolated by single cell sorting and capable of expressing membrane-bound as well as secreted human IgG were directly screened during antibody discovery, not only for high affinity binding to human ROR2, but also functionally as ADCs using a cytotoxicity assay with a secondary anti-human IgG-toxin-conjugate. Using this strategy, we identified and validated twelve fully human, monoclonal anti-human ROR2 antibodies with nanomolar affinities that are highly potent as ADCs and could be promising candidates for the therapy of human cancer. The screening for functional and internalizing antibodies during the early phase of antibody discovery demonstrates the utility of the mammalian cell-based Transpo-mAb Display platform to select for functional binders and as a powerful tool to improve the efficiency for the development of therapeutically relevant ADCs.